Defining ecological and sociological integrity for the South Platte River Basin - Woodring, R. Craig, editor; Roberts, Jennifer, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1993)
South Platte Forum (3rd: 1993: Fort Collins, Colo.).
R. Craig Woodring, editor, Jennifer Roberts, asst. editor.
Partial proceedings of the 3rd South Platte Forum.
Held October 27-28, 1992, University Holiday Inn, Fort Collins, Colorado.
Keywords: Water resources development -- South Platte River Valley (Colo. and Neb.) -- Congresses; Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Ecological integrity -- Congresses